EVOLUTION OF TRIBAL MOVEMENTS AND THE EMERGENCE OF STATEHOOD IN JHARKHAND - Chakraborty, Madhumita; Kesharwani, Pradeep Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The Santhals, Mundas, Oraons, and Hos are just a few of the Jharkhand tribes that have a strong connection to their own social structures, customs, and cultural heritage. Their spiritual practices, festivals, rituals, and languages all contribute to their unique identity and help to keep their legacy alive. An essential part of the cultural expression of the tribes of this area is the different languages they speak, which include Santali, Mundari, Kurukh, and Ho. Their social governing institutions, like the Parha and ancient panchayats, keep the community together, while celebratory activities, like the Santhals' Sohrai art and the Oraons' Sarhul festival, showcase their creative and spiritual riches. Additionally, the indigenous people's sustainable lifestyle choices, such as their agricultural and forest management techniques, demonstrate a profound familiarity with and respect for their natural surroundings. A strong sense of identity and resistance activities against colonial control have allowed them to retain cultural continuity while confronting problems like as colonial exploitation, urbanization, and cultural degradation. The lasting impact of influential figures such as Jaipal Singh Munda, who was instrumental in the fight for Jharkhand's statehood, highlights the continuous endeavors to safeguard tribal rights and maintain their cultural heritage in the face of a dynamic and unpredictable environment. Tribal communities maintain their unique identity and establish their position within the larger national framework via cultural activities, educational programs, and legal safeguards.